Written corrective feedback in teaching writing: a review of theory, research and practice - Nodistya Septian Indrastana (Politeknik Negeri Jember, 2018)
Linguistic errors are ubiquitous in the writing products of second and foreign language students. Errors in writing, therefore, have been a major concern to teachers or students in both English as Second Language (ESL) and English as Foreign Language (EFL) settings. Accordingly, error correction has been a central topic in second language (L2) teaching, especially writing. As such, written corrective feedback (WCF) has been an inviting topic of attraction for both L2 writing researchers and practitioners. Through a narrative review, this paper attempts to shed light on current and relevant theories of WCF, summarize several existing studies about WCF, and propose its practical application in teaching writing, especially in L2 higher education context. Keywords: written corrective feedback, teaching writing, higher education context, theoretical review